Prevalence of Thyroid Disorders among Pregnant and Non-Pregnant Women Attending a Tertiary Care Center in Kathmandu (Nepal Medical College Journal, 2024)
Thyroid hormones are crucial for the overall development of the fetus, and their impact on the pregnancy outcomes needs to be considered seriously. Hence, universal screening for thyroid disorders is recommended in the first trimester of pregnancy. One hundred pregnant women in their first trimester and 100 non-pregnant women of the reproductive age group were screened for thyroid function test. The prevalence of thyroid disorders among the total participants was 32.0% of which 23.5% were hypothyroid and 8.5% were hyperthyroid. Pregnant females had a significantly higher prevalence of thyroid disorders (46.0%) than non-pregnant counterparts (18.0%; P